Die vrou Wysheid, God, en ekobillikheid: Liggaamsideologie in Spreuke 8:1–9:18 - Venter, Philip P. (HTS teologiese studies, 2009)
The woman Wisdom, God, and ecojustice: Ideology of the body in Proverbs 8:1–9:18This article examines the ideology of the body, specifically in terms of the gender of Wisdom and God, from an ecojustice perspective. Femininity within a God construct could contribute to a value system that incorporates compassion, interrelatedness and mutual care. In Proverbs 8:1–9:18, however, the woman Wisdom does not represent an ecofriendly construct, but simply enhances and supports the patriarchal, masculine values incorporated in the God Yahweh.